Alkaloids from Lepidium meyenii (Maca), structural revision of macaridine and UPLC-MS/MS feature-based molecular networking. (October 2021) - Le, Hien T.N.; Van Roy, Elias; Dendooven, Ella; Peeters, Laura; Theunis, Mart; Foubert, Kenn; Pieters, Luc; Tuenter, Emmy
Abstract: Lepidium meyenii Walp., known as Peruvian ginseng, is widely used in ethnomedicine. To date, L. meyenii is cultivated worldwide at high-altitude and is commonly used as a food supplement. However, its medicinal value is still controversial and its mechanism of action remains unknown, due to limited knowledge about the phytochemical constituents of this plant species. In this study, a multidisciplinary approach comprising conventional NMR- and HRMS-based structure elucidation, quantum mechanical calculation of NMR chemical shifts and UPLC-MS/MS feature-based molecular networking was applied to analyse the phytochemical profile of L. meyenii . In the current work, three previously undescribed imidazole alkaloids were identified using extensive spectroscopic techniques (HRMS, NMR), for which the names lepidiline E, F and G were adopted. In addition, two amidine alkaloids were reported, representing an undescribed class of alkaloids in L. meyenii, and 1, 2, 3, 4-tetrahydro- β -carboline-3-carboxylic acid, a well-known β -carboline alkaloid, was also isolated from L. meyenii for the first time. Molecular networks of imidazole, amidine and β -carboline alkaloids in L. meyenii were constructed by the Global Natural Products Social Molecular Networking (GNPS) web platform, resulting in the tentative identification of three undescribed analogues. In addition, the structure of a previously reported compound named 'macaridine' was revised as macapyrrolin C based on density functional theory (DFT) calculations and comprehensive comparison of NMR data. Graphical abstract: Image 1 Highlights: Three alkaloids were identified for the first time. Three undescribed analogues were characterized by LC-MS/MS molecular networking. Two amidine alkaloids were reported, representing a new class of alkaloids in L. meyenii. 1, 2, 3, 4-tetrahydro- β -carboline-3-carboxylic acid, was isolated from L. meyenii for the first time. The structure of 'macaridine' was revised as macapyrrolin C using DFT calculations.